Information Technology Services: A Key Knowledge-Intensive Business Service Industry in Hong Kong SAR, China. (March 2014) - Hu, Mei-Chih; Sharif, Naubahar; Baark, Erik
As the global economy focuses increasingly on Asia, Hong Kong's role as an intermediary between China and the rest of the world merits investigation. In view of the increasing importance of knowledge-based business services and Hong Kong's recent drive to promote innovation and high-tech services, economists and policy makers must understand Hong Kong's capacity to support economic development in the Asian region. Following a theoretically informed discussion of the role of information technology (IT) services within the broader category of knowledge-intensive business services (KIBS), Hong Kong's IT services sector is described and analysed to determine its potential for supporting an innovative local services environment and to identify the key opportunities and challenges involved in further developing the sector. In-depth interviews of important actors in the IT services sector in Hong Kong and case studies of firms that have leveraged IT services supplement our analysis of data on IT service production and usage. IT services represents an opportunity through which Hong Kong can use targeted policy to drive growth and expand and deepen economic relations with Mainland China.